EVALUASI PEMANFAATAN RUANG TERBUKA HIJAU TAMAN NUKILA KOTA TERNATE - Rizky Nurhalizah Karim; Fabiola B. Saroinsong; Josephus ., Kalangi (Sam Ratulangi University, 2021)
This study aims to evaluate the utilization of Nukila Park green open space, Ternate City, by the people of Ternate City, both socially, economically, and ecologically. The method used in this study is a quantitative descriptive method. The tools and materials used are questionnaires, sound level meters, cameras, anemometers, writing instruments, thermohygrometers, and satellite images. The results of interviews conducted on 100 respondents showed that the Nukila Park green open space provided great benefits to the people of Ternate City with a visit percentage of 73% because of its good ecological quality, comfortable level of comfort and adequate facilities. Nukila Park Green Open Space has 17 types of vegetation consisting of 11 types of trees and 12 types of saplings. The benefits of Nukila Park green open space from the socio-cultural aspect are as a meeting place for direct communication, gathering for certain activities, a place to relax or rest (sit/eat), a place for education and learning about nature. from the ecological aspect, namely the thermal comfort felt by the respondents and biodiversity.